Sorafenib and everolimus in patients with advanced solid tumors and KRAS‐mutated NSCLC: A phase I trial with early pharmacodynamic FDG‐PET assessment. (21st May 2020) - Nogova, Lucia; Mattonet, Christian; Scheffler, Matthias; Taubert, Max; Gardizi, Masyar; Sos, Martin L.; Michels, Sebastian; Fischer, Rieke N.; Limburg, Meike; Abdulla, Diana S.Y.; Persigehl, Thorsten; Kobe, Carsten; et al.
Abstract: Background: Treatment of patients with solid tumors and KRAS mutations remains disappointing. One option is the combined inhibition of pathways involved in RAF‐MEK‐ERK and PI3K‐AKT‐mTOR. Methods: Patients with relapsed solid tumors were treated with escalating doses of everolimus (E) 2.5‐10.0 mg/d in a 14‐day run‐in phase followed by combination therapy with sorafenib (S) 800 mg/d from day 15. KRAS mutational status was assessed retrospectively in the escalation phase. Extension phase included KRAS‐mutated non–small‐cell lung cancer (NSCLC) only. Pharmacokinetic analyses were accompanied by pharmacodynamics assessment of E by FDG‐PET. Efficacy was assessed by CT scans every 6 weeks of combination. Results: Of 31 evaluable patients, 15 had KRAS mutation, 4 patients were negative for KRAS mutation, and the KRAS status remained unknown in 12 patients. Dose‐limiting toxicity (DLT) was not reached. The maximum tolerated dose (MTD) was defined as 7.5 mg/d E + 800 mg/d S due to toxicities at previous dose level (10 mg/d E + 800 mg/d S) including leucopenia/thrombopenia III° and pneumonia III° occurring after the DLT interval. The metabolic response rate in FDG‐PET was 17% on day 5 and 20% on day 14. No patient reached partial response in CT scan. Median progression free survival (PFS) and overall survival (OS) were 3.25 and 5.85 months, respectively. Conclusions: Treatment of patients with relapsed solid tumors with 7.5 mg/d E and 800 mg/d S is safe and feasible. Early metabolic response in FDG‐PET was not confirmed in CT scan several weeks later. The combination of S and E is obviously not sufficient to induce durable responses in patients with KRAS‐mutant solid tumors. Abstract : The study investigated the combination of sorafenib and everolimus in patients with solid tumors (dose escalation part) and KRAS mutated NSCLC (expansion part). Although the trial showed manageable safety profile of sorafenib and everolimus, it failed in providing long terms responses for patients with solid tumors and KRAS mutated NSCLC. The novelty of the study was the early pharmacodynamics assessment using FDG‐PET implemented in a phase‐I.